Quadriceps autograft to treat Achilles Chronic tears: a simple surgical technique. Issue 1 (December 2016) - Arriaza, Rafael; Gayoso, Raquel; López-Vidriero, Emilio; Aizpurúa, Jesús; Agrasar, Carlos
Abstract Background Chronic Achilles tendon tears could hinder patients and represent a challenge to surgeons. Although many different surgical techniques have been proposed for reconstruction of a neglected Achilles tendon rupture, there is no clear evidence to support one technique over the others, but the use of a technique that could allow for an "anatomical" reconstructions seems desirable. Methods The present paper describes a new anatomic Achilles tendon reconstruction for chronic tears, using a quadriceps tendon autograft as graft source, with PRP injected into the graft and the neighbor tissue, and fixation in a bone trough with a simple small fragments screw. Results Autologous quadriceps tendon graft seems an excellent option, although -surprisingly- has received little attention until now. Conclusions Autologous Quadriceps tendon graft (in bone-tendon configuration) is a simple technique that could allow surgeons to reconstruct tissue defects in the Achilles tendon with non-expensive hardware.